New-onset childhood extensive cutaneous lichen planus following asymptomatic COVID-19 infection: report of a case - Fatemeh Ansari Asl; Mozhdeh Sepaskhah; Marzie Rassafian; Fatemeh Sari Aslani; Farideh Jowkar (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The objective of this study was to describe a case of cutaneous lichen planus (LP) that appeared following COVID-19 infection. Case description: We report a case of extensive cutaneous classic familial LP in a 4-year-old male child after an asymptomatic serologically confirmed COVID-19 infection. The patient developed intensely itchy, purple, flat-topped papules and plaques, mainly on the dorsal surface of the hands, feet, forearms, and shins. Histopathological examination of the skin biopsy showed vacuolar and apoptotic degeneration of the basal cell layer with a band-like lymphocyte infiltrate at the dermo-epidermal junction and confirmed the diagnosis of LP. Comments: LP could be considered among the differential diagnoses of pediatric post-COVID inflammatory skin lesions, either in the patients recovering from COVID-19 infection or in the suspicious asymptomatic cases in close contact with COVID-19-infected patients.